DNA damage in outdoor workers occupationally exposed to environmental air pollutants. Issue 4 (23rd March 2006) - Tovalin, H; Valverde, M; Morandi, M T; Blanco, S; Whitehead, L; Rojas, E
Abstract : Background: Health concerns about the exposure to genotoxic and carcinogenic agents in the air are particularly significant for outdoor workers in less developed countries. Aims: To investigate the association between personal exposure to a group of air pollutants and severity of DNA damage in outdoor workers from two Mexican cities. Methods: DNA damage (Comet assay) and personal exposure to volatile organic compounds, PM2.5, and ozone were investigated in 55 outdoor and indoor workers from México City and Puebla. Results: In México City, outdoor workers had greater DNA damage, reflected by a longer tail length, than indoor workers (median 46.8 v 30.1 μm), and a greater percentage of highly damaged cells (cells with tail length ⩾41 μm); in Puebla, outdoor and indoor workers had similar DNA damage. There were more alkali labile sites in outdoor than indoor workers. The DNA damage magnitude was positively correlated with PM2.5 and ozone exposure. Outdoor and indoor workers with ⩾60% of highly damaged cells (highly damaged workers) had significantly higher exposures to PM2.5, ozone, and some volatile organic compounds. The main factors associated with the highly damaged workers were ozone, PM2.5, and 1-ethyl-2-methyl benzene exposure. Conclusions: With this approach, the effects of some air pollutants could be correlated with biological endpoints from the Comet assay. It is suggested that the use of personal exposure assessment and biological endpoints evaluation could be an important tool to generate a more precise assessment of the associated potential health risks.